Relationships Between Depressive Symptoms, Interpersonal Sensitivity and Social Support of Employees Before and During the COVID-19 Epidemic: A Cross-lag Study - Mei, Songli; Meng, Cuicui; Hu, Yueyang; Guo, Xinmeng; Lv, Jianping; Qin, Zeying; Liang, Leilei; Li, Chuanen; Fei, Junsong; Cao, Ruilin; Hu, Yuanchao (Frontiers in Psychology, 2022)
This study examined the correlation between depressive symptom, interpersonal sensitivity and social support before and during COVID-19 and verified the causal relationship among them. The study used Social Support Scale (SSRS) and Symptom Self-Rating Scale (SCL-90) to investigate relevant variables. A total of 1,414 employees from enterprises were recruited for this longitudinal study, which a follow up study was conducted on the same group of participants one year later. Paired sample t-test results showed that significant differences were only found in social support, not in depressive symptoms or interpersonal sensitivity. The results of correlation analysis showed that social support, depressive symptom and interpersonal sensitivity were significantly correlated between wave 1 and wave 2. The cross-lag autoregressive pathway showed that employees' social support level, depressive symptom and interpersonal sensitivity all showed moderate stability. Crossing paths showed that wave 1 social support could significantly predict wave 2 depression symptom (β=-0.21 P<0.001) and wave 2 interpersonal sensitivity (β=-0.21 P<0.001). Wave 1 depressive symptom (β=-0.10 P<0.01) could significantly predict wave 2 social support, while wave 1 interpersonal sensitivity (β=0.07 P=0.10) could not predict wave 2 social support. social support can be considered as a protective factor against mental health problems.